DAMPAK PEMBANGUNAN SARANA DAN PRASARANA TERHADAP PENINGKATAN KUALITAS PROSES BELAJAR SISWA DI SMA KRISTEN KETAPANG 1 JAKARTA - Anita Jojor (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2022)
Presentation of data on the impact of building facilities and infrastructure on the quality of student learning at SMA Kristen Ketapang1 Jakarta. To obtain data using quantitative methods as many as 110 people, with a population of six classes divided into MIPA and IPS majors. A sample of 10% is taken from the specified population. By using the purposive sampling method, 11 students attended the Ketapang 1 Jakarta Christian School from KB-TK to SMA. Data acquisition techniques are carried out through observation, surveys, and documentation. The product-moment correlation equation was used to analyze the data. From the research output it is accepted that the hypothesis (Ha) uses the interpretation that the impact of infrastructure development and infrastructure on the quality of the student learning process at SMA Kristen Ketapang1 Jakarta is classified as high using a coefficient interval of 0.629 more than the